Pengaruh Pendapatan dan Beban Operasional terhadap Laba Bersih pada PT Astra Graphia Tbk yang Terdaftar di Bursa Efek Indonesia Periode 2013 – 2022 - Maryana, Ela; Sarjana, Samuel Horas (JURNAL ECONOMINA, 2024)
This study aims to determine the effect of operating income and expenses on net profit at PT Astra Graphia Tbk which is listed on the Indonesian Stock Exchange for the period 2013 – 2022. The population of this research is the financial statements of PT Astra Graphia Tbk and 40 data samples are taken. Based on the nature of the data used in this study is a type of quantitative research. The data collection technique used in this research was literature study and published data on www.idn.co.id. Data testing was carried out using the multiple linear regression method, classical assumption test, t test, F test, coefficient of determination and correlation. (R-Square) using SPSS for Windows 25 software. The results show that income has a significant and significant effect on net income. This is evidenced by the sig. of 0.006 <0.05 and the calculated value of t 2.939 > t table 2.026. Operating expenses have no significant effect on net income. This is evidenced by the sig. of 0.502 > 0.05 and the calculated value of t -0.678 <t table 2.026. Thus, the company needs to pay attention to the value of operating income and expenses each period, because this affects the net profit of the company.